MODERN WAYS TO IMPROVE THE FINANCING OF INVESTMENT ACTIVITIES OF JOINT STOCK COMPANIES (Academia Science Repository, 2023)
Joint stock companies play a crucial role in driving economic growth and development by engaging in investment activities that stimulate innovation, create job opportunities, and generate wealth. Financing these investment activities is a critical aspect that determines the success and sustainability of joint stock companies. In recent years, various modern approaches have emerged to enhance the financing of investment activities for such companies. This article aims to explore these modern ways and highlight their benefits and implications.